Age and cigarette smoking modulate the relationship between pulmonary function and arterial stiffness in heart failure patients. Issue 10 (March 2017) - Li, Li; Hu, Bangchuan; Gong, Shijin; Yu, Yihua; Yan, Jing
Abstract : Abstract: The aim of this study was to assess the relationship between arterial stiffness and pulmonary function in chronic heart failure (CHF). Outpatients previously diagnosed as CHF were enrolled between April 2008 and March 2010, and submitted to arterial stiffness measurement and lung function assessment. Spirometry was performed by measuring forced vital capacity (FVC), the fraction of predicted FVC, forced expiratory volume in 1 second (FEV1 ), the percentage of predicted FEV1 in 1 second, FEV1 to FVC ratio, and the percentage of predicted FEV1 /FVC. Cardio-ankle vascular index (CAVI) was considered for the estimation of arterial stiffness. The 354 patients assessed included 315 nonsmokers, and were 68.2 ± 7.2 years' old. Unadjusted correlation analyses demonstrated CAVI was positively related to age ( r  = 0.3664, P  < 0.0001), and negatively related to body mass index (BMI, r  = −0.2040, P  = 0.0001), E/A ratio ( r  = −0.1759, P  = 0.0010), and FEV1 ( r  = −0.2987, P  < 0.0001). Stepwise multivariate regression analyses showed age ( r 2  = 0.2391, P  < 0.0001), BMI ( r 2  = −0.2139, P  < 0.0001), smoking ( r 2  = 0.1211, P  = 0.0130), E/A ratio ( r 2  = −0.1082, P  = 0.0386), and FEV1 ( r 2  = −0.2550, P  < 0.0001) were independent determinants of CAVI. In addition, there is a significant interaction between CAVI and forced expiratory volume in 1 second (FEV1 ) in relation to age ( P int  < 0.0001) and smoking ( P int  = 0.0001). Meanwhile, pulmonary function was not associated with BMI or E/A ratio. These findings demonstrated that reduced pulmonary function is associated with the increased CAVI, and had an interactive effect with age and smoking on CAVI in patients with CHF.